Penggunaan Metode Rough Set Pada Pola Minat Dan Bakat Siswa Dalam Menentukan Tema P5: Studi Kasus : SMPS Esa Prakarsa - Febi Andini; Relita Buaton; Imeldawaty Gultom (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
This research aims to identify the patterns of students' interests and talents at Esa Prakarsa Junior High School and apply the Rough Set method in data analysis to determine the most appropriate theme of the Pancasila Student Profile Strengthening Project (P5). The study involved data collection from 178 students through a questionnaire designed to explore their interests and talents. The results of the analysis showed a significant correlation between the patterns of interest and talents of students with the selection of the P5 theme. The Rough Set method successfully identified relevant rules, such as students who have an interest in the field of art are more suitable for the theme of sustainable lifestyle, while talented students in the field of sports are more in line with the theme of Build the Soul and Body. The use of Rosetta software in data analysis provides recommendations for interesting and relevant P5 themes, supporting the achievement of national education goals in forming a young generation with character and competence. This research is expected to provide guidance for schools in developing P5 themes that are more relevant and interesting for students, as well as improving learning outcomes based on their interest and talent characteristics.